2015
DOI: 10.1097/id.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization and In Vivo Evaluation of Dual Acid-Etched and Grit-Blasted/Acid-Etched Implants in Sheep

Abstract: Overall, improved bone-to-implant response was observed for the AA implant surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Based on our results, etching with HCl and H 2 O 2 seems to be an effective technique to modify Ti surface, due to its improved corrosion behavior in all electrolytes evaluated as well as good surface characteristics after the corrosion process. Our results also provided important inside about the higher in vivo success rate of dental implants treated with acid etching when compared to machined and sandblasted ones [86][87][88]. Therefore, in a nutshell, the lower corrosion stability of sandblasted surfaces may be a driven force toward increased failure of dental implants in a clinical scenario.…”
Section: Discussionmentioning
confidence: 61%
“…Based on our results, etching with HCl and H 2 O 2 seems to be an effective technique to modify Ti surface, due to its improved corrosion behavior in all electrolytes evaluated as well as good surface characteristics after the corrosion process. Our results also provided important inside about the higher in vivo success rate of dental implants treated with acid etching when compared to machined and sandblasted ones [86][87][88]. Therefore, in a nutshell, the lower corrosion stability of sandblasted surfaces may be a driven force toward increased failure of dental implants in a clinical scenario.…”
Section: Discussionmentioning
confidence: 61%
“…The iliac crest site offers the advantages of bone characteristics, the absence of postoperative morbidity, and the ability to conduct a high number of implants test simultaneously; however, although the iliac crest exhibits low bone density, the cortical is thicker relative to the thin cortical of the posterior region of the maxilla, which also shows low bone density. Previous studies- 30,33,36,45 that used sheep models have reported that the animals were euthanized at the end of the experiments; in our study, all animals were kept alive and healthy. The insertion torque value is a direct measure of the bone's cutting resistance during implant insertion surgery.…”
Section: Dovepressmentioning
confidence: 84%
“…The pelvic animal model was used for all experiments according to previous research. 30,[33][34][35][36] The cranial part of each animal's right iliac wing (n = 5/group) received all implants ( Figure 1). Five implants were installed in each animal, but only three were used for this study.…”
Section: Surgical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that improved boneto-implant response was observed for the acid-etched implant surface. [18,19] One case report has mentioned the use of the citric acid but without using hydrogen peroxide at 3%. The effect of citric acid on the implant surface is not new; however, we suggest that the complementary use of hydrogen peroxide and citric acid has enhanced the alveolar bone healing and the activation of a new re-osseointegration process.…”
Section: Discussionmentioning
confidence: 99%